Phenobarbital induced erythroderma: a case report - Gurappanavar, Deepika; Manchukonda, Ravishankar; Shivamurthy, Shwetha (International Journal of Basic & Clinical Pharmacology, 2017)
Phenobarbital (PHB) (International Non-proprietary Name) or Phenobarbitone (British Approved Name) is a long acting barbiturate and the most widely used anti-seizure medication globally. Fever, skin reactions, limb edema, and drug-induced hypersensitivity have been reported in children because of various drugs, mainly aromatic antiepileptic drugs such as phenytoin, PHB, carbamazepine, and primidone. The skin reactions differ in severity and range from a mild maculopapular erythema to exfoliative dermatitis. A 2-month-old male baby was brought to the dermatology out-patient department with complaints of redness and scaling all over the body (erythroderma) after 2-3 weeks of PHB treatment for convulsions. PHB was stopped, and corticosteroids (topical and systemic) were started. The baby improved over a period of 2 weeks. According to Naranjo’s adverse drug reaction probability scale, the causality relation between erythroderma and PHB was found to be a probable one.